Degradable polyphosphoester-based silver-loaded nanoparticles as therapeutics for bacterial lung infections1. Issue 6 (14th February 2015) - Zhang, Fuwu; Smolen, Justin A.; Zhang, Shiyi; Li, Richen; Shah, Parth N.; Cho, Sangho; Wang, Hai; Raymond, Jeffery E.; Cannon, Carolyn L.; Wooley, Karen L.
<x xml:space="preserve">Abstract</x> Degradable polyphosphoester-based polymeric nanoparticles carrying silver cations via interactions with alkyne groups has been developed for lung infections.